Critical Incident Stress Debriefing as a Trauma Intervention in First Nation Communities - Hughes, Megan L. (Canadian Journal of Counselling and Psychotherapy, 2007)
This study examines the appropriateness of a cross-cultural application of Critical Incident Stress Debriefing (CISD). Participant/observations were made of CISD workshops conducted for First Nations participants. The facilitator and five participants were interviewed using narrative methodology. Observations and interview data were examined using narrative analysis. Results suggest that CISD is not suitable for this population. It lacks First Nations content, structure, and orientation. Its short-term nature conflicts with the First Nations population’s multigenerational, culturally pervasive trauma. Implications include examining cross-cultural applications of western interventions, documenting the therapeutic needs of First Nations populations, using qualitative methodology with CISD, and further research of CISD.